(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: This study aimed (1) to describe the condition of the organizational structure and quality of public services in the Department of Population and Civil Registration Regency of North Halmahera. (2) to analyze the effect of organizational structure on the quality of public services in the Department of Population and Civil Registration North Halmahera Regency. This research uses descriptive method with quantitative approach. Samples were drawn by purposive sampling of respondents as many as 33 employees / personnel services, and 33 other respondents are elements of service recipients, then spread Questionnaire (questionnaire) and the results are analyzed by applying descriptive statistical analysis techniques and simple regression analysis and correlation of product moment. Results of the study were presented as follows: (1) Organizational Structure Office of Population and Civil North Halmahera Regency is in the category "medium" or reasonably support the achievement of the quality of public services, while the quality of public services, according to respondents element employees perceive higher than respondents element of the user community services which can only perceive the "moderate" or medium. (2) The organizational structure has positive influence on the quality of public services. That means that if the organizational structure optimally managed, it will boost the quality of public services, particularly in the Department of Population and Civil North Halmahera. Thus, it can be concluded that the hypothesis which states "The organizational structure of positive and significant impact on the quality of public services at the Department of Population and Civil North Halmahera validity can be tested empirically, as well as justify terori-the underlying theory. Keywords: organizational structure, quality of public service